2007
DOI: 10.1128/cvi.00289-07
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Tracking of Cytokines after Acute Exposure to Tuberculosis: Association of Distinct Cytokine Patterns with Protection and Disease Development

Abstract: Household contacts (HCs) of patients with tuberculosis (TB) are at higher risk of infection as well as the development of active disease. Longitudinal tracking of antigen-specific cytokines after acute exposure may significantly advance our understanding of the dynamic changes in cytokine patterns associated with disease establishment. To achieve this objective, we carried out a prospective cohort study with healthy HCs after exposure to TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 46 publications
4
36
0
Order By: Relevance
“…The time course for responses to CF in our cohort is similar to that seen in a HHC study in Pakistan where IFN-γ reached a plateau after 6 months. 24 The Ag85B protein is primarily a stimulus for CD4+ T cells and its rapid response may in part reflect boosting of memory response primed by BCG vaccination or environmental mycobacteria that also can express Ag85B. Additionally, NK T cells, part of innate immune responses, can produce IFN-γ in response to CF and whole MTB, but not to defined antigens such as Ag85B.…”
Section: Discussionmentioning
confidence: 99%
“…The time course for responses to CF in our cohort is similar to that seen in a HHC study in Pakistan where IFN-γ reached a plateau after 6 months. 24 The Ag85B protein is primarily a stimulus for CD4+ T cells and its rapid response may in part reflect boosting of memory response primed by BCG vaccination or environmental mycobacteria that also can express Ag85B. Additionally, NK T cells, part of innate immune responses, can produce IFN-γ in response to CF and whole MTB, but not to defined antigens such as Ag85B.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown, in animal models, that a decreased production of IFN-c and a decrease in the number of IFN-c-producing cells are predictive of an increased risk of developing TB [40]. In contact patients, it has been observed that the progression to disease was associated with a decrease in IFN-c, and an increase in interleukin (IL)-10 and IL-4 levels [41,42]. Some data suggest that in individuals with a recent exposure to TB, the protective response shifts from Th1 to Th2, even before the clinical symptoms appear [43].…”
Section: Discussionmentioning
confidence: 99%
“…As Pakistan has a very high incidence of TB at 181/100,000 population (50), the possibility of exposure to M. tuberculosis cannot be ruled out, nor can exposure to environmental mycobacteria. Recent studies of household contacts of patients with TB show that the time postexposure at which the IFN-␥ response to M. tuberculosis is measured determines the cytokine profile obtained (23).…”
Section: Discussionmentioning
confidence: 99%